Devil in the details? Developmental dyslexia and visual long-term memory for details - Huestegge, Lynn; Rohrßen, Julia; van Ermingen-Marbach, Muna; Pape-Neumann, Julia; Heim, Stefan (Frontiers in Psychology, 2014)
Cognitive theories on causes of developmental dyslexia can be divided into language-specific and general accounts. While the former assume that words are special in that associated processing problems are rooted in language-related cognition (e.g., phonology) deficits, the latter propose that dyslexia is rather rooted in a general impairment of cognitive (e.g., visual and/or auditory) processing streams. In the present study, we examined to what extent dyslexia (typically characterized by poor orthographic representations) may be associated with a general deficit in visual long-term memory for details. We compared object- and detail-related visual long-term memory performance (and phonological skills) between dyslexic primary school children and IQ-, age- and gender-matched controls. The results revealed that while the overall amount of long-term memory errors was comparable between groups, dyslexic children exhibited a greater portion of detail-related errors. The results suggest that not only phonological, but also general visual resolution deficits in long-term memory may play an important role in developmental dyslexia.